2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649394
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a Wireless Body Area sensor network for remote patient monitoring

Abstract: In recent years, interests in the application of Wireless Body Area Network (WBAN) have grown considerably. A WBAN can be used to develop a patient monitoring system which offers flexibility and mobility to patients. Use of a WBAN will also allow the flexibility of setting up a remote monitoring system via either the internet or an intranet. For such medical systems it is very important that a WBAN can collect and transmit data reliably, and in a timely manner to the monitoring entity. In this paper we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 4 publications
0
60
0
Order By: Relevance
“…The obtained simulation results in all considered cases (see Figure 5, 6 and 7) speak in favor of the applied modulation scheme, path loss and noise models, so they can be employed as a sound basis for further, more extensive, analysis in this domain. The trade-off between BPSK and QPSK modulation schemes is simulated, as well, and it is observed that the BER is slightly lower in the case of BPSK, but it is negligible in terms of the transmitted data amount which is doubled by using QPSK [24,[32][33][34][35].…”
Section: Simulation Analysismentioning
confidence: 99%
“…The obtained simulation results in all considered cases (see Figure 5, 6 and 7) speak in favor of the applied modulation scheme, path loss and noise models, so they can be employed as a sound basis for further, more extensive, analysis in this domain. The trade-off between BPSK and QPSK modulation schemes is simulated, as well, and it is observed that the BER is slightly lower in the case of BPSK, but it is negligible in terms of the transmitted data amount which is doubled by using QPSK [24,[32][33][34][35].…”
Section: Simulation Analysismentioning
confidence: 99%
“…The lack of mobility caused by wired monitoring systems is discussed by Baisa [3]. Although some wireless monitoring systems have been proposed [4,5], they are being introduced in hospital wards which potentially impact on a number of issues including privacy.…”
Section: Technology Reviewmentioning
confidence: 99%
“…Events detected by the ECG are converted into packets and then stored in a data buffer. The characteristics [19][20][21][22] and the QoS requirements [23] of the ECG are summarized in Table I. We assume that the process of communication between the ECG and the BNC can be done directly and without interference.…”
Section: A Simulation Considerations and Setupmentioning
confidence: 99%